SYSTEMATIC REVIEW ON MEDICAMENTS USED IN MANAGEMENT OF DIABETES MELLITUS - JAMWAL, ANUPAM (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Diabetes has a global prevalence in developed countries and rapidly flexing its roots in middle-and low-income countries. According to the World Health Organization, it is a major cause of kidney collapse, heart problems, and lower limb amputation. Diabetes mellitus is a metabolic disorder showing an uncontrolled increase in blood glucose levels. To date, no permanent cure has been developed for the complete restoration of impaired glucose haemostasis. With the use of therapeutic agents and nontherapeutic agents, glucose levels can be kept in control for a very long time. The foremost goal of all current ongoing treatments is to control high blood glucose levels, reduction in elevated lipid levels, and delay in the progression of diabetes-related complications. Various therapeutics agents are developed in recent decades, which shown very promising results in the management of diabetes mellitus. These agents prescribed after reviewing the clinical symptoms and situation of an individual patient. This review compiles noteworthy information related to clinically approved medicaments for diabetes mellitus. Review emphasis on categorization, mechanism of action, noted adverse effects along with the physiological responses of used medicines to treat diabetes mellitus.